(untitled) (Research, Society and Development, 2023)
From the 5th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-V), autism has been called Autism Spectrum Disorder (ASD) and is characterized as a neurodevelopmental disorder that results in impaired communication, behavior and social interaction. The diagnosis is made through clinical criteria and should occur early in order to improve the prognosis of the patient. The present study aimed to evaluate the knowledge of medical students at a university in the state of Santa Catarina/Brazil in relation to autism. This is an exploratory and descriptive study with a quantitative approach and non-probabilistic sample with students of the clinical cycle and medical internship. Data were collected through a pre-structured and validated questionnaire, which was translated and adapted by the authors to measure technical-scientific knowledge about autism. From the analyzed questionnaires, it was noted that most of the students had already had contact with an individual with ASD and had good knowledge about their clinical condition. However, the data reveal an important knowledge gap among medical students regarding the already demythologized relationship between autism and vaccination and the main tools for screening the disease. Furthermore, most students do not feel prepared to care for a person with the disorder and their family members, so that quality interventional educational actions, unquestionably, can increase and improve the knowledge and confidence of medical students.